Understanding Students’ Struggles in Solving Mathematical Problems: A Systematic Literature Review Using Polya’s Framework - A, Abdul Wahab; Kusuma, Yaya S; Juandi, Dadang; Turmudi, Turmudi; Buhaerah, Buhaerah; Syaiful, Syaiful (FKIP Universitas Lampung, 2024)
Understanding Students' Struggles in Solving Mathematical Problems: A Systematic Literature Review Using Polya’s Framework. Objective: This study aims to identify the specific challenges faced by students in solving mathematical problems at each stage of Polya's problem-solving framework: understanding the problem, devising a plan, carrying out the plan, and looking back. Methods: The research focuses on the context of mathematics education in Indonesia, using a systematic literature review (SLR) methodology. A total of 48 articles published in accredited journals (2019–2023) were systematically analyzed, based on inclusion criteria that involved Polya’s framework, the education levels of elementary to high school, and mathematical problem-solving contexts. Findings: Challenges at the understanding the problem stage include low motivation, lack of concentration, poor reading literacy, weak mathematical communication, conceptual misunderstandings, and reasoning deficiencies. In the devising a plan stage, students struggle with cognitive gaps, misconceptions, weak connections between mathematical concepts, difficulties in mathematical modeling, and lack of organizational skills. At the carrying out the plan stage, procedural errors, misconceptions, and inaccuracy are the primary obstacles. Finally, at the looking back stage, motivational issues, inadequate evaluation, errors in interpreting results, and lack of thoroughness persist. Conclusion: This research highlights the need for targeted teaching strategies, such as strengthening students' reading literacy, addressing misconceptions, and fostering deeper conceptual understanding through collaborative and problem-based learning. Furthermore, the study emphasizes designing interventions tailored to each stage of Polya's framework to enhance students’ problem-solving abilities in mathematics education. Keywords: systematic literature review, mathematical problem solving, polya framework, student challenges.DOI: http://dx.doi.org/10.23960/jpp.v14.i3.2024118